Changes of gut microbiota in colorectal cancer patients with Pentatrichomonas hominis infection - Zhang, Hongbo; Yu, Yanhui; Li, Jianhua; Gong, Pengtao; Wang, Xiaocen; Li, Xin; Cheng, Yidan; Yu, Xiuyan; Zhang, Nan; Zhang, Xichen (Frontiers in Cellular and Infection Microbiology, 2022)
Pentatrichomonas hominis is a parasitic trichomonads protozoa that parasitizes in the colon and cecum of humans and other animals. Our previous studies have demonstrated that infection with P. hominis is associated with the incidence of colon cancer (37.93%). However, the mechanism by which P. hominis infections increase the incidence of colon cancer remains unclear. Previous studies have suggested that certain parasites promote colon cancer by regulating gut microbiota. This study aimed to elucidate whether the association between P. hominis infections and the increased incidence of colon cancer is related to changes in gut microbiota. Therefore, the gut microbiota patients with colon cancer who were infected with P. hominis and uninfected patients with colon cancer were analyzed by 16S rRNA high-throughput sequencing. The results demonstrated that patients with colon cancer who were not infected with P. hominis showed increased gut bacterial diversity, a higher relative abundance of Alcaligenes sp., Leucobacter sp., Paraprevotella sp., Ruminococcaceae UCG-002, and a significant reduction in the abundance of Veillonella sp., compared to individuals without colon cancer. Additionally, the relative abundance of the Ruminococcaceae UCG-002 and the Eubacterium eligens groups was reduced, while the relative abundance of bacteria associated with colon cancer, including Flavonifractor sp., Lachnoclostridium sp., and the Ruminococcus gnavus group, increased significantly in patients with colon cancer who were infected with P. hominis, compared to those of uninfected patients with colon cancer. In conclusion, these results suggested that P. hominis infections may aggravate the development of colon cancer and the findings provide new insights for subsequent in-depth studies on the pathogenesis, diagnosis, and prevention of colon cancer.